Considering the ways in which anti-oppressive practice principles can inform health research. (February 2015) - Baines, Sue; Edwards, Jane
Highlights: Research requires attention to history, contemporary workings and future potentials. Past decades recounted a history of abuse and oppression within health research. Anti-oppressive practice provides us with a way of addressing privilege in our work. Integrating anti-oppressive practices within research can address oppression. Abstract: All research that investigates therapeutic practice should be conducted with the aim to develop and support good procedures of inquiry. An anti-oppressive practice approach within health research provides a way to systematically examine research procedures and motivations to increase the potential that the resultant research will yield ethical and just results. In this paper two music therapy researchers consider how anti-oppressive practices can address real life problems and be applicable to real life situations; from questions of participation, to developing the research question, recruitment, consent, and further steps of the research process. The goal of this paper is to examine issues arising when considering anti-oppressive practices and healthcare research practices from the perspective of the authors' experience of music therapy research.